Springtails (Collembola, Hexapoda) from Montebello Lakes, Chiapas, Mexico. Issue 3 (3rd July 2018) - Palacios-Vargas, José G.; Cortés-Guzmán, Daniela; Alcocer, Javier
ABSTRACT: Springtails are mostly terrestrial organisms, relatively rare in truly aquatic environments; a few are neustonic while others are found in humid caves, surfaces, and crevices of marine coastal zones. We have found them in the benthic zone of 4 deep lakes, Bosque Azul, Dos Lagos, Ensueño, and Tziscao of Lagunas de Montebello National Park in Chiapas. We recovered 43 specimens belonging to 13 species from the samples, all of which except Americabrya arida were first records for the state of Chiapas; the most abundant were A. arida and Lepidocyrtus lanuginosus . Species richness of each lake varied between 1 and 12; density varied between 15 ± 25 and 133 ± 118 org m −2, and biomass varied between 0.02 and 4.3 ± 4.4 and 0.02 μg m −2 . Tziscao showed the highest abundance (35 individuals), species richness (12 species), and density (133 ± 118 org m −2 ), and Bosque Azul showed the highest average biomass (4.3 ± 4.4 μg). Together, 96% of the organisms were collected during summer when lakes were thermally stratified (warm monomixis); 44% of the organisms were recovered from deep anoxic samples (>20 m). Springtails were found living in warm waters in conditions varying from well oxygenated to anoxic, a slightly basic pH range (7.1–8.3), and a high range of electric conductivity (219.7–1716.0 μS cm −1 ) values. Sediments were mainly composed of sands and mud (silt and clay) with a wide organic matter range (15.4–51.2%) and sedimentary carbonates (6.0–98.3%). Of the 43 specimens, 17 were adults (12 males and 5 females) and 26 were immature, both with gut content composed mostly of Cladosporium hyphae and conidia. These are the first records of submerged Collembola inhabiting the deep benthic zones of Mexican lakes.